Methylprednisolone alleviates cognitive functions through the regulation of neuroinflammation in Alzheimer’s disease - Sun, Yuan; Li, Jinran; A, Nan; Li, Zhaoxing; Zhong, Wenyi; Chen, Long; Liu, Sai; Zhang, Bocheng; Zhu, Zheying; Li, Xinuo (Frontiers in Immunology, 2023)
Alzheimer's disease (AD) is a progressive neurodegenerative disease and linked to abnormal deposition of amyloid-β (Aβ), neurofibrillary tangles (NFTs), synaptic dysfunction, and neuroinflammation. Despite significant progress in unravelling the pathogenesis of AD, currently main therapeutic interventions is limited to symptomatic alleviation. Methylprednisolone (MP), a synthetic glucocorticoid, is recognised for its extensive anti-inflammatory properties. Our study assessed the neuroprotective effect of MP (25 mg/kg) administrationed to an Aβ1-42-induced AD mouse model. Our findings demonstrate that MP treatment can ameliorate cognitive impairment in Aβ1-42-induced AD mice and suppress microglial activation in the cortex and hippocampus. RNA-Sequencing analysis reveals that MP ultimately rescues cognitive dysfunction through improving the synapse function and inhibiting the immune and inflammatory processes. Our study suggests that MP could be a promising drug alternative for the treatment of AD, either alone or in combination with other existing drugs.